The Spirituality of Justification. (March 2014) - Peters, Ted
Abstract The doctrine of justification‐by‐faith has gathered enough dust on its shelf in the museum of antiquated doctrines. When we draw justification‐by‐faith out where we can take a good look at it, it glistens like a mirror. It reflects back to us human beings who we are. We are self‐justifiers. In the name of justice, we perpetrate violence. The pursuit of justice does as much damage as the pursuit of injustice, unfortunately. Like a mirror, justification‐by‐faith reveals who we are and announces that God justifies us by grace. This means we do not have to self‐justify. Liberated from self‐justification, the Christian is free to love for the sake of the beloved.